Exploration of photocatalytic activity of an end-on azide bridged one-dimensional cadmium(II) Schiff base complex for the degradation of organic dye in visible light. (10th January 2017) - Roy, Sumit; Harms, Klaus; Bauzá, Antonio; Frontera, Antonio; Chattopadhyay, Shouvik
Graphical abstract: One new photo-luminescent polynuclear cadmium(II) complex with salicylaldimine Schiff base ligand and azide as co-ligand has been synthesized and characterized. The structure has been confirmed by single crystal X-ray analysis. Under visible light irradiation, the complex can acts as a highly efficient photocatalyst for the decomposition of organic dye. Abstract: A one-dimensional polynuclear end-on azide bridged octahedral cadmium(II) Schiff base complex, [{CdL(μ-1, 1-N3 )}2 Cd(μ-1, 1-N3 )2 ·1.76CH3 OH] n {HL = 2-(3-(dimethylamino)propyliminomethyl)-6-ethoxyphenol} has been synthesized and characterized by single crystal X-ray crystallography. The complex crystallizes in monoclinic space group C 2/ c with cell dimensions, a  = 21.4706(8) Å, b  = 9.9542(4) Å, c  = 19.3257(7) Å, β  = 103.7819(11)°. Extended supra-molecular assemblies were generated through weak non-covalent interactions. The energetic features of these interactions have also been studied by means of DFT calculations. The complex exhibits good photoluminescence in DMSO medium. The application of the complex as a photocatalyst for the decomposition of organic dye in visible light has been explored.